The Emerging Role of the Prokineticins and Homeobox Genes in the Vascularization of the Placenta: Physiological and Pathological Aspects - Alfaidy, Nadia; Brouillet, Sophie; Rajaraman, Gayathri; Kalionis, Bill; Hoffmann, Pascale; Barjat, Tiphaine; Benharouga, Mohamed; Murthi, Padma (Frontiers in Physiology, 2020)
Vasculogenesis and angiogenesis are key processes of placental development, which occur throughout pregnancy. Placental vasculogenesis occurs during the first trimester of pregnancy culminating in the formation of hemangioblasts from intra-villous stem cells. Placental angiogenesis occurs subsequently, forming new blood vessels from existing ones. Angiogenesis also takes place at the fetomaternal interface, allowing essential spiral arteriole remodelling to establish the fetomaternal circulation. Vasculogenesis and angiogenesis in animal models and in humans have been studied in a wide variety of in vitro, physiological and pathological conditions, with a focus on the pro- and anti-angiogenic factors that control these processes. Recent studies revealed roles for new families of proteins, including direct participants such as the prokineticin family, and regulators of these processes such as the homeobox genes. This review summarizes recent advances in understanding the molecular mechanisms of actions of these families of proteins. Over the past decade, evidence suggests increased production of placental anti-angiogenic factors, as well as angiogenic factors are associated with fetal growth restriction (FGR) and preeclampsia (PE): the most threatening pathologies of human pregnancy with systemic vascular dysfunction. This review also reports novel clinical strategies targeting members of these family of proteins to treat PE and its consequent effects on the maternal vascular system.